1997
DOI: 10.1111/j.1365-2133.1997.tb03759.x
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma-associated paraneoplastic retinopathy: case report and review of the literature

Abstract: A 51-year-old white male suffering from metastatic malignant melanoma of the skin presented with lymph node metastases and paraneoplastic retinopathy 4 years after resection of the primary tumour. There were no cerebral metastases. Ocular symptoms consisting of night blindness and sensations of 'shimmering lights' persisted after total resection of the inguinal lymph node metastases and administration of dacarbazine and prednisone. Perimetry of both eyes was abnormal with concentric restriction. Electroretinog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…16 Moreover, the difference in the level of this dysfunction could explain why retinal degenerations are not always found in both eyes of MAR patients. 10,12 Using our mouse melanoma model, we also found that only 62% of affected animals had retinopathy in both eyes.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…16 Moreover, the difference in the level of this dysfunction could explain why retinal degenerations are not always found in both eyes of MAR patients. 10,12 Using our mouse melanoma model, we also found that only 62% of affected animals had retinopathy in both eyes.…”
Section: Discussionmentioning
confidence: 65%
“…We found that melanoma-bearing mice showed similar signs of retina degeneration as reported for MAR patients, including the reduction of aand b-waves, degeneration of photoreceptor cells, bipolar cells and pigment epithelium. [8][9][10][11][12][13] Since this retina degeneration in tumor-bearing mice appeared to be a paraneoplastic event, which was independent from any ocular tumor invasion and from overexpression of the ret transgene, we suggested that ret transgenic mice could be a good animal model of MAR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…blurred vision. The question was whether the patient had melanoma-associated retinopathy [31], an early interferon-associated retinopathy or an anterior ischemic optic neuropathy after interferon treatment. A melanoma-associated retinopathy was excluded by a conventional electroretinogram of the rods and cones and by a normal subjective night vision.…”
Section: Discussionmentioning
confidence: 99%